American aurora: environment and apocalypse in the life of Johannes Kelpius - Grieve-Carlson, Timothy (Oxford studies in Western esotericism, 2024)
"American Aurora explores the impact of climate change on early modern radical religious groups during the height of the Little Ice Age in the seventeenth century. Hermetic, alchemical, and esoteric texts became crucial sources of religious meaning and perspective among radical Protestants during this period as they struggled to understand their changing climate and a cosmos that seemed to be declaring its own decline. In particular, American Aurora focuses on the life and legacy of Johannes Kelpius (1667-1707), an enormously influential but comprehensively misunderstood theologian who settled outside of Philadelphia from 1694 to 1707. American Aurora explores the Hermetic and alchemical dimensions of Kelpius's Christianity before turning to his legacy in American religion and literature. This includes original translations of Kelpius's university writings-which have never before been translated into English-along with other important sources from the period in German and Latin. By the eighteenth and nineteenth centuries, Kelpius's legacy began to warp under the scrutiny of both Enlightenment historians and antiquarian authors, entangling him in the legacies of nineteenth century Rosicrucianism and the occult revival. American Aurora points toward a time and place when climate change caused an eruption of esoteric thought and practice-and how this moment has been largely forgotten"--